Foxp3 expression in lymph node metastases in patients with head and neck cancer. (2nd November 2017) - Boduc, Mehtap; Roessler, Marion; Mandic, Robert; Netzer, Christoph; Güldner, Christian; Walliczek-Dworschak, Ute; Stuck, Boris A.; Mandapathil, Magis
Abstract: Introduction: The prevalence and activity of regulatory T cells in patients with cancer correlates with poor prognosis. These cells are characterized by their expression of Forkhead box protein-3 (Foxp3). Squamous cell carcinoma is the most prevalent type of cancer in the head and neck region with overall poor survival rates, also due to early spread of metastatic cells. Material and methods: Primary tumor specimens as well as lymph node specimens harvested during neck dissection of 65 patients with a diagnosis of HNSCC were subjected to immunohistochemical and H-score analysis of Foxp3 expression. Demographics, diagnoses, histopathology and subsequent outcome were analyzed. Results: The primary cancer was squamous cell carcinoma in all patients (male/female 55:10) with the following tumor locations: oral cavity n = 16, oropharynx n = 28, hypopharynx n = 11 and larynx n = 10 (Stage III n = 18; Stage IVA n = 45; Stage IVB n = 2). The H-score for Foxp3 expression in the primary lesion as well as metastatic lymph nodes was significantly higher in advanced stages compared to early stages with differences among tumor locations, which were not significant. High Foxp3 expression was associated with inferior overall survival rates at a mean follow-up of 83.4 months (6–204 months) Conclusions: Foxp3 expression in HNSCC varied from the anatomical site and correlated positively with tumor stage and was associated with poor prognosis. Therefore, Foxp3 expressions in primary lesions as well as lymphogenic metastases appear to predict high-risk HSNCC patients. Novel therapeutic approaches targeting Foxp3 + cells might seem promising for this patient population.